Influence of carbohydrate on immune function following 2 h cycling - Nieman, D. C.; Henson, D. A.; Gojanovich, G.; Davis, J. M.; Murphy, E. A.; Mayer, E. P.; Pearce, S.; Dumke, C. L.; Utter, A. C.; McAnulty, S. R.; McAnulty, L. S. (Research in Sports Medicine, 2006)
The influence of carbohydrate compared with placebo ingestion on changes in immune cell counts and functions following 2 h intensive cycling was studied in 12 trained cyclists who functioned as their own controls. The subjects performed two tests 2 weeks apart where they cycled for 2 h at ~64% Wattsmax while receiving 4 mL·kg-1·15 min-1 carbohydrate (6%) (Cho) or placebo (Pla) beverages. Blood samples were collected 30 min preexercise, and immediately and 1 h postexercise. The samples were assayed for plasma cortisol and epinephrine, blood leukocyte subset counts, PHA-induced lymphocyte proliferation, and natural killer cell activity (NKCA). Compared with Pla ingestion, Cho attenuated exercise-induced changes in plasma cortisol, blood neutrophil, and monocyte counts, but not in total blood lymphocyte, T cell, and NK cell counts, PHA-induced lymphocyte proliferation, and NKCA. Thus despite a strong attenuating influence of carbohydrate ingestion on exercise-induced changes in plasma cortisol and blood neutrophil and monocyte counts, other immune measures related to lymphocyte subset counts, and function were unaffected.